(untitled) (Journal of Comparative & International Higher Education, 2022)
Cyberspace has become a fixture of contemporary higher education institutions. When facing challenges seeking admission to a foreign university, international students often resort to online resources for guidance. By engaging in these online activities, international students develop a sense of community and identity. Despite recent advancement, existing studies on digital space and international students often fail to address the contentious nature of the community-forming process. Using digital ethnography and interviews, I studied an online forum for Taiwanese international students, STUDYABROAD, to delineate how social networking sites (SNSs) help reinforce group boundaries relating to different class traits and individual characteristics. International students find support and reassurance by socializing with netizen members and learning essential knowledge and information, but they also learn to distinguish different personalities and associate with them based on how they are perceived. By describing how Taiwanese students interpret online forums and develop norms around those communities, this study contributes to a growing strand of research into socialization of the international online community.